If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 59 + -1(2c + 3) = (4c + 7) + c Reorder the terms: 59 + -1(3 + 2c) = (4c + 7) + c 59 + (3 * -1 + 2c * -1) = (4c + 7) + c 59 + (-3 + -2c) = (4c + 7) + c Combine like terms: 59 + -3 = 56 56 + -2c = (4c + 7) + c Reorder the terms: 56 + -2c = (7 + 4c) + c Remove parenthesis around (7 + 4c) 56 + -2c = 7 + 4c + c Combine like terms: 4c + c = 5c 56 + -2c = 7 + 5c Solving 56 + -2c = 7 + 5c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5c' to each side of the equation. 56 + -2c + -5c = 7 + 5c + -5c Combine like terms: -2c + -5c = -7c 56 + -7c = 7 + 5c + -5c Combine like terms: 5c + -5c = 0 56 + -7c = 7 + 0 56 + -7c = 7 Add '-56' to each side of the equation. 56 + -56 + -7c = 7 + -56 Combine like terms: 56 + -56 = 0 0 + -7c = 7 + -56 -7c = 7 + -56 Combine like terms: 7 + -56 = -49 -7c = -49 Divide each side by '-7'. c = 7 Simplifying c = 7
| 9a-4+3(a-11)m=23 | | 7c-7=4c-17 | | -3p+8=5-(7p+3) | | 2+2=17 | | 22ab^3*-1a^10= | | (4x+3)=31 | | d+0.02d=520 | | y+15=2y | | (4x+3)(7-4)= | | 3(n-4)=4(n-3) | | 3(x-1)=18-2(x+3) | | 0.8=0.57g | | 2.25(4x-4)=9x+10 | | 7x+5-x=46 | | 4y+2=6y-8 | | 7a=a | | 5(y+30)=10 | | 4x+2=6y-8 | | 7(-3+2)=35 | | 1n-18-7n=-9 | | y=2lnx-3lnx | | -2(4-2x)=-16+2x | | 2(2x-5)=8x-6 | | y=-(-6)-(-6)-6(-6)-8 | | (4+5x)=74 | | -32=-12+k | | 22ab^3*-a^9= | | X+2+x+2+2x+2x= | | (7y+3v)(6y-5v-4)=0 | | x^2-8y+4=0 | | -5.2*f=36.4 | | 4xy+6yx= |